Cost-Effectiveness Analysis of Pembrolizumab Plus Chemotherapy vs. Chemotherapy Alone as First-Line Treatment in Patients With Esophageal Squamous Cell Carcinoma and PD-L1 CPS of 10 or More - Zheng, Zhiwei; Lin, Jingrong; Zhu, Huide; Cai, Hongfu (Frontiers in Public Health, 2022)
Background: This study was aimed to analyze the economics of pembrolizumab plus chemotherapy as first-line treatment in patients with esophageal squamous cell carcinoma(ESCC) and PD-L1 CPS of 10 or more in China Methods: Basis on the advanced ESCC of the KEYNOTE-590 clinical trial data, a Markov model was performed to simulate the clinical course and evaluate the patient’s total lifetime, total costs, quality-adjusted life-years (QALYs), incremental cost-effectiveness ratio (ICER) for pembrolizumab plus chemotherapy (cisplatin and 5-fluorouracil) versus chemotherapy alone in first-line treatment of ESCC and PD-L1 CPS of 10 or more. Utility values and direct costs related to the treatments were gathered from the published literature data. One-way and probability sensitivity analyses were conducted to check the stability in the model. Results: The baseline analysis indicated that the incremental effectiveness and cost of pembrolizumab plus chemotherapy versus chemotherapy alone added 1.23 QALYs and resulted in an incremental cost of 51320.22,which had an ICER of 41805.12/QALY, higher than the willingness-to-pay (WTP) threshold of China (31,498.70/QALY). Sensitivity analysis demonstrated that the ICERs were most sensitive to the cycle of pembrolizumab used and the cost of pembrolizumab. Conclusion: The result of our present analysis suggested that addition of pembrolizumab plus chemotherapy as first-line treatment might not be cost-effective for patients with ESCC and PD-L1 CPS of 10 or more in China.